1997
DOI: 10.1001/jama.1997.03540380054031
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Decisions About Hormone Replacement Therapy in Postmenopausal Women

Abstract: The benefit of hormone replacement therapy in reducing the likelihood of developing CHD appears to outweigh the risk of breast cancer for nearly all women in whom this treatment might be considered. Our analysis supports the broader use of hormone replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 186 publications
(42 citation statements)
references
References 90 publications
0
37
0
5
Order By: Relevance
“…American women were prescribed and consumed hormone replacement therapy to relieve menopausal symptoms, with the added belief that HRT might also prevent heart disease, osteoporosis, and stroke (e.g., Col et al 1997). In 1999, the popularity of HRT surged once again with the introduction of a new combination pill of estrogen and progesterone (cHRT), which was seen as safer and more effective at controlling menopausal symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…American women were prescribed and consumed hormone replacement therapy to relieve menopausal symptoms, with the added belief that HRT might also prevent heart disease, osteoporosis, and stroke (e.g., Col et al 1997). In 1999, the popularity of HRT surged once again with the introduction of a new combination pill of estrogen and progesterone (cHRT), which was seen as safer and more effective at controlling menopausal symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In 1997, a mathematical model of several epidemiological studies concluded that the benefit from CVD provided by hormone therapy far outweighed the potential risks and recommended a broader use of hormone therapy in postmenopausal women (Col et al, 1997). Scarcely a decade later, the Women's Health Initiative (WHI) study yielded just the opposite recommendation, namely that hormone therapy should be given in the smallest dose possible for the shortest amount of time and should not be prescribed for cardiovascular protection (FDA statement posted 8/13/2002).…”
mentioning
confidence: 99%
“…In three cases, the findings of DA and matching SR of RCTs were similar after the sensitivity analysis [14,16,27]. …”
Section: Resultsmentioning
confidence: 92%